Association Between Diabetes and Vertical Bone Defects in Periodontitis Using Cone Beam Computed Tomography: A Cross-Sectional Study in the Eastern Province, Saudi Arabia - Eman Aljoghaiman; Abdullah Alzahrani; Rakan Albarqi; Saad Alqbbani; Hamad Alshiddi; Mishali AlSharief; Mohammed Alsaati; Faisal E. Al Jofi (Clinics and Practice)
Background: The association between diabetes and periodontal disease is well established, but its impact on intrabony periodontal defects remains unclear. Aims: This study examines the relationship between diabetes and intrabony periodontal defects using cone beam computed tomography (CBCT). Methods: A retrospective analysis of 99 CBCT images from Imam Abdurrahman bin Faisal University (2010–2022) was conducted. Intrabony periodontal defects were assessed, and logistic regression was used to analyze their association with diabetes. Results: Intrabony periodontal defects were detected in 66% of the sample, with 36% exhibiting multiple defects. Crude logistic regression showed a significant association between diabetes and intrabony periodontal defects (OR 3.986, 95% CI 1.454–10.922) and defect count (OR 3.382, 95% CI 1.430–8.003). However, multiple regression analysis did not confirm diabetes as an independent predictor (adjusted OR 0.740, 95% CI 0.087–6.314). Conclusions: Diabetes was not significantly associated with the prevalence or number of intrabony periodontal defects after adjusting for the confounders. However, these findings highlight the multifactorial nature of periodontal bone loss and the need for comprehensive patient assessment. Clinically, this underscores the importance of integrating both systemic and local periodontal evaluations in diabetic patients to improve early detection and personalized treatment planning. Further research with larger, more diverse samples and integrated clinical assessments is needed to refine our understanding of this relationship and enhance patient management.